Good Policing Trust, Legitimacy and Authority. - Hough, Mike (Policy Press, 2020)
Renowned criminologist Mike Hough considers how the police service might build trust, legitimacy and compliance with the law in this important book. He challenges conventional thinking on crime, contrasts 'hard' and 'soft' policing styles and offers a fresh approach that secures compliance with the law through ethical policing.